X

= x

= x(x

= (x

Factors of x

are (x

9 - 4xy - y

x = {-b + √(b

x = {-4y + √(16y

x = {-4y + √(12y

x = {-4y + √12(y

x = {-4y + √2*2*3(y

x = {-4y + 2√3(y

x = 2{-2y + √3(y

x = -2y + √3(y

Factors of 9 - 4xy - y

^{2}- x + 2= x

^{2 }- 2x + x + 2= x(x

^{ }- 2) + (x - 2)= (x

^{ }- 2)(x + 1)Factors of x

^{2}- x + 2are (x

^{ }- 2) and (x + 1)9 - 4xy - y

^{2 }- x^{2}x = {-b + √(b

^{2}- 4ac)}/2ax = {-4y + √(16y

^{2}- 4(1)(y^{2}- 9)}/2(1)x = {-4y + √(12y

^{2}+ 36)}/2x = {-4y + √12(y

^{2}+ 3)}/2x = {-4y + √2*2*3(y

^{2}+ 3)}/2x = {-4y + 2√3(y

^{2}+ 3)}/2x = 2{-2y + √3(y

^{2}+ 3)}/2x = -2y + √3(y

^{2}+ 3)Factors of 9 - 4xy - y

^{2 }- x^{2 }are {-2y + √3(y^{2}+ 3)} and {-2y - √3(y^{2}+ 3)}